2020
DOI: 10.5847/wjem.j.1920-8642.2020.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sepsis on hippocampal volume and memory function

Abstract: BACKGROUND: This study aimed to determine the effects of sepsis on brain integrity, memory, and executive function. METHODS: Twenty sepsis patients who were not diagnosed with sepsis-associated encephalopathy (SAE) but had abnormal electroencephalograms (EEGs) were included. The control group included twenty healthy persons. A neuropsychological test of memory and executive function and a brain magnetic resonance imaging scan were performed. The volumes of cortex and subcortex were measured using the FreeSurfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Besides, complex I is potentially more vulnerable to neuronal injury than other ETS components, and the level of pyridine nucleotide and other cofactors is also reduced during sepsis. There is also evidence that the hippocampus is more susceptible to insults, such as ischemia, anoxia, inflammation and sepsis ( 56 ). Therefore, a functional difference in distinct brain regions, particularly after BBB injury, cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, complex I is potentially more vulnerable to neuronal injury than other ETS components, and the level of pyridine nucleotide and other cofactors is also reduced during sepsis. There is also evidence that the hippocampus is more susceptible to insults, such as ischemia, anoxia, inflammation and sepsis ( 56 ). Therefore, a functional difference in distinct brain regions, particularly after BBB injury, cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Current guidelines recommend the use of norepinephrine (NE) as a fi rst-line vasoactive agent, but its effect on intestinal microcirculation remains controversial. Nantais et al [35] reported that NE could improve intestinal microcirculation dysfunction; while Nacul et al [36] found that NE could aggravate or have no significant effect on intestinal microcirculation dysfunction. Dopexamine, dopamine, and dobutamine are used alone, and the combination of dobutamine and NE is thought to improve intestinal microcirculation dysfunction.…”
Section: Vasoactive Drugsmentioning
confidence: 99%
“…The pathogenesis of sepsis is extremely complicated due to the dysregulation of the body's response to infection [3][4][5]. In sepsis, immune dysfunction, coagulation dysfunction, and systemic inflammatory network effect induce damage to its tissues and organs [6][7][8][9]. The mechanism of brain impairment among patients with sepsis was still unclear, and brain injury could increase the risk of mortality in septic patients.…”
Section: Introductionmentioning
confidence: 99%